2021
DOI: 10.1177/0018726721998743
|View full text |Cite
|
Sign up to set email alerts
|

Decoding secrecy as multiple temporal processes: Co-constitution of concealment and revelation in archival stories

Abstract: How can we understand secrecy as temporal processes in organization? How can we address the inherent dynamics between concealment and revelation over time? In this paper, we build on an inherent and yet overlooked character of secrecy as temporal and explores temporalization processes of secrecy. We suggest that secrecy should be reconceptualized as processes of simultaneous concealment and revelation in multiple temporalities. Drawing on such temporal sensitivity, we apply a history-laden analysis of four exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…The performativity of secrecy and transparency has been noted in previous works, describing how transparency measures and rituals produce new types of opacity (Albu and Flyverbom, 2019;Christensen and Cornelissen, 2015;Fenster, 2006;Ringel, 2019), how secrecy involves revelation (Fan and Grey, 2021;Fan and Liu, 2022) and keeps reappearing in new guises (Owetschkin and Berger, 2019), and how both secrecy and transparency are needed to compensate for each other's deficiencies (Bok, 1982). Yet, the performative dynamics of the secrecy-transparency relationship remains unspecified.…”
Section: Introductionmentioning
confidence: 93%
“…The performativity of secrecy and transparency has been noted in previous works, describing how transparency measures and rituals produce new types of opacity (Albu and Flyverbom, 2019;Christensen and Cornelissen, 2015;Fenster, 2006;Ringel, 2019), how secrecy involves revelation (Fan and Grey, 2021;Fan and Liu, 2022) and keeps reappearing in new guises (Owetschkin and Berger, 2019), and how both secrecy and transparency are needed to compensate for each other's deficiencies (Bok, 1982). Yet, the performative dynamics of the secrecy-transparency relationship remains unspecified.…”
Section: Introductionmentioning
confidence: 93%
“…Secrecy is an attitude that enables battered women to conceal their DV experiences (Emery et al., 2020). Secrets have been conceptualized in and through multiple temporalities, where secrets exist not only in concealment but also in disclosure (Fan & Liu, 2021). Krasmann (2019) observed that secrets are fugitives, coming into being in the very moment they get disclosed.…”
Section: Research Themesmentioning
confidence: 99%
“…Krasmann (2019) observed that secrets are fugitives, coming into being in the very moment they get disclosed. Once disclosed, the secret does not disappear, but rather continues and takes on a different form, growing in a way that continues to be cloaked in secrecy, giving secrets characteristics of continuity and simultaneity (Fan & Liu, 2021; Krasmann, 2019). Simon‐Kumar et al.…”
Section: Research Themesmentioning
confidence: 99%
See 2 more Smart Citations